The Prognostic Impact of the Metastatic Lymph Nodes Ratio in Colorectal Cancer - Zhang, Chi-Hao; Li, Yan-Yan; Zhang, Qing-Wei; Biondi, Alberto; Fico, Valeria; Persiani, Roberto; Ni, Xiao-Chun; Luo, Meng (Frontiers in Oncology, 2018)
Background: This study was designed to validate the prognostic significance of the ratio of positive to examined lymph nodes (LNR) in patients with colorectal cancer. Methods: 218,314 patients from the SEER database and 1,811 patients from the three independent multicenter were included in this study. The patients were divided into 5 groups on a basis of previous published LNR: LNR0, patients with no metastatic lymph nodes; LNR1, patients with the LNR between 0.1 and 0.17; LNR2, patients with the LNR between 0.18 and 0.41; LNR3, patients with the LNR between 0.42 and 0.69; LNR4, patients with the LNR greater than 0.7. The 5-year OS and CSS rate were estimated using Kaplan-Meier method and the survival difference was tested using log-rank test. Multivariate Cox analysis was used to further assess the influence of the LNR on patients’ outcome. Results: The 5-year OS rate of patients within LNR0 to LNR4 group was 71.2%, 55.8%, 39.3%, 22.6% and 14.6%, respectively (p<0.001) in the SEER database. While the 5-year OS rate of those with LNR0 to LNR4 was 75.2%, 66.1%, 48.0%, 34.0% and 17.7%, respectively (p<0.001) in the international multicenter cohort. In the multivariate analysis, LNR was demonstrated to be a strong prognostic factor in patients with <12 and ≥12 metastatic lymph nodes. Furthermore, the LNR had a similar impact on the patients’ prognosis in colon cancer and rectal cancer. Conclusion: The LNR allowed better prognostic stratification than the positive node (pN) in patients with colorectal cancer and the cut-off values were well validated.